(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
هدفت الدراسة إلى التعرف على مدى ممارسة الأنشطة الابتكارية في الحلقة الأولىمن التعليم الأساسي في محافظة اللاذقية، وتكونت العينة من(140) تلميذاً من تلاميذ الصف الرابع في مدارس عدةفي المدينة والريف في محافظة اللاذقية، موزعين كالتالي (70)تلميذاً وتلميذة من ثلاث مدارس في المدينة، و(70) تلميذاً وتلميذة من سبع مدارس في الريف،وتم استخدام قائمة تورانس للأنشطة الابتكارية كأداة للدراسة، والمكونة من أربعة جوانب (اللغوي، والعلمي، والفني، والاجتماعي). وأظهرت النتائج وجود أثر دال إحصائياً بين متوسط درجات أفراد العينة في جوانب القائمة(اللغوي، والعلمي، والفني، والاجتماعي والدرجة الكلية)،وأوصت الدراسة بالاهتمام بالأنشطة الابتكارية من حيث الوقت والإمكانات لأنها من العناصر المهمة في العملية التعليمية وإعطاء أهمية للأنشطة الابتكارية في المناهج الدراسيةوتنميتها لدى تلاميذ الحلقة الأولى بوصفها مرحلة نمو مهمة وتأسيسية. This study tries to identify the extent of the practice of innovative activities in the first episode of basic education in the province of Lattakia. The sample consisted of 140 students from fourth grade students in several schools in the city and countryside in the province of Lattakia, distributed as follows: (70) pupils from three schools in the city, and (70) pupils from seven schools in the countryside. Torrance’s list of innovative activities is used as a tool in the study. It is composed of four aspects (linguistic, scientific, and technical, and social). Results showed existence of a statistically significant difference between the average scores of the sample in the aspects of the menu (linguistic, scientific, technical, social, and total score). The study suggests that attention should be paid to innovative activities in terms of time and the potential in school curricula of first episode as pupils of this cycle are given constitutive basic educational training.